GEOMORPHOLOGY AND NATURAL HAZARD IN THE COASTAL ZONE OF THACH HAN RIVER MOUTH - Quan, Nguyen Cong; Hung, Pham Van; Dung, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2018)
Study on the geomorphological features, landform changes and correlated natural hazardous events was based on analyzing available literature and data. The coastal landform of Thach Han river mouth is a result from fluvial, fluvial - marine and marine accumulation along with local tectonic activities during Pliocene - Quaternary. During Pliocene - Pleistocene, western uplift and eastern subsidence movements were forming the types of landforms such as hills, erosion and abrasion terraces and accumulated plains of fluvial and fluvial - marine sediments. From early to middle Holocene, subsidence movements and fluvial, fluvial - marine and marine accumulation formed 4 types of accumulated plains as follows: Fluvial - marine plain in the central part, marine plains extending to the north and south of the studied area. From late Holocene to present, differentiated tectonic movements and fluvial and fluvial - marine accumulation have formed 6 types of different landforms (fluvial, lacustrine, marshy and marine origins ...etc.). Morphodynamic processes including erosion and sedimentation are natural hazards which cause damage to economy and people's life in the coatal zone of Thach Han river mouth. The erosion has been scattered along the banks of the Thach Han and Cam Lo rivers, at Gio Viet, Gio Mai, Trieu Giang, Ai Tu, and coastal erosion occurred north of Cua Viet.